Application of Restorative Justice Approach in Handling Cases of Alleged Medical Malpractice by the Police: Study at The North Sumatra Police - Franshery Malau, Togu; Kusbianto, Kusbianto; Maysarah, Andi (STAINI Press, 2026)
The restorative justice approach represents a contemporary paradigm within the Indonesian criminal justice system that emphasizes the resolution of criminal cases through the restoration of relationships between victims, offenders, and the community in a proportional manner. This approach is particularly relevant in handling alleged medical malpractice cases, considering their close connection to professional negligence and the legal relationship between medical practitioners and patients. This study aims to analyze the legal framework governing the application of restorative justice in criminal case handling, specifically alleged medical malpractice cases by the police, and to examine its implementation during the investigation and inquiry stages at the North Sumatra Regional Police. In addition, this research identifies the obstacles faced by law enforcement authorities in applying the restorative justice approach. The research method employed is normative juridical research combined with an empirical approach, conducted through literature review and interviews with police officers. The findings indicate that, from a normative perspective, the police possess an adequate legal basis to implement restorative justice. However, in practice, several challenges remain, including limited public understanding, differing perceptions among victims, the complexity of medical evidence, and caution among law enforcement officers in exercising discretion. Therefore, strengthening technical regulations and enhancing investigators’ capacity are necessary to ensure effective and equitable implementation.